Maintenance schedule optimization based on distribution characteristics of the extreme temperature and relative humidity of Cave 87 in the Mogao Grottoes - Yanjie Zhang; Yajun Wang (Heritage Science, 2023)
Abstract Frequent fluctuations in microclimate inevitably cause serious irreversible damage to cultural heritage (such as high risks of cracking, flaking, salt efflorescence, swelling, disaggregation, surface layer detachment, and even microbe diseases). For the caves closed to the visitors, specifying a more rational schedule to minimize human influences on the microclimate is urgent and significant for daily maintenance of the Mogao Grottoes. Interior microclimate fluctuations are caused by air convection between the inside and outside environments, which is highly related to internal and external microclimate differences. Therefore, the occurrence times of the extreme values of temperature (T), relative humidity (RH), T difference (inside T minus outside T), and RH difference (inside RH minus outside RH) between the inside and outside environments of Cave 87 were analysed. The results indicated that the times of the extreme T/RH and T/RH differences showed obvious seasonal characteristics. From April to September, both the daily minimum T and RH differences mainly occurred from 8 am ~ 11 am, and the maximum differences were observed from 16 pm ~ 21 pm. This indicates that door openings for daily investigation and maintenance should be arranged in the morning rather than in the afternoon. The times of the daily extreme T and RH differences occurred from 16 pm ~ 19 pm (minimum) and 8 am ~ 11 am (maximum) from January ~ March and October ~ December, and the door opening time should be accordingly optimized. The analysis results provide more reasonable and specific door opening times for Cave 87 and a scientific reference for preventive conservation of the Mogao Grottoes.